Pengaruh Content Marketing Terhadap Minat Beli Tiket pada PT. KAI: Studi pada Content Trip Experience di Sosial Media Instagram @kai121_ - Fitriana Albertina; Cecep Safa'atul Barkah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Digital strategies are becoming increasingly important in today's digital market, with social media platforms like Instagram being used for communication, information exchange, and marketing. Indonesia is an ideal location for content marketing, as over 60% of its clientele consists of millennials or Generation Z. PT. Kereta Api Indonesia (Persero) targets urbanites through its social media marketing initiatives, with content marketing being a fundamental element of their strategy. The Trip Experience category generates the most interaction, attracting customers to engage with the organization's products. This research aims to examine the impact of content marketing on consumer purchasing propensity. Descriptive verification was used, and a nonprobability sampling strategy was used. Coefficients of determination, simple linear regression tests, and hypothesis testing were used to investigate the effect. The Slovin method was used to select 100 individuals who followed @kai121_ and participated in the